Comparison of BAP65, DECAF, PEARL, and MEWS Scores in Predicting Respiratory Support Need in Hospitalized Exacerbation of Chronic Obstructive Lung Disease Patients - Acet-Öztürk, Nilüfer Aylin; Aydin-Güçlü, Özge; Yildiz, Merve Nur; Demirdöğen, Ezgi; Görek Dilektaşli, Aslı; Coşkun, Funda; Uzaslan, Esra; Ursavaş, Ahmet; Karadağ, Mehmet (Medical principles and practice, 2024)
Abstract Objective: Prognostic models aid clinical practice with decision-making on treatment and hospitalization in exacerbation of chronic obstructive lung disease (ECOPD). Although there are many studies with prognostic models, diagnostic accuracy is variable within and between models. Subjects and Methods: We compared the prognostic performance of the BAP65 score, DECAF score, PEARL score, and modified early warning score (MEWS) in hospitalized patients with ECOPD, to estimate ventilatory support need. Results: This cross-sectional study consisted of 139 patients. Patients in need of noninvasive or invasive mechanical ventilation support are grouped as ventilatory support groups (n = 54). Comparison between receiver operating characteristic curves revealed that the DECAF score is significantly superior to the PEARL score (p = 0.04) in discriminating patients in need of ventilatory support. DECAF score with a cutoff value of 1 presented the highest sensitivity and BAP65 score with a cutoff value of 2 presented the highest specificity in predicting ventilatory support need. Multivariable analysis revealed that gender played a significant role in COPD exacerbation outcome, and arterial pCO2 and RDW measurements were also predictors of ventilatory support need. Within severity indexes, only the DECAF score was independently associated with the outcome. One-point increase in DECAF score created a 1.43 times higher risk of ventilatory support need. All severity indexes showed a correlation with age, comorbidity index, and dyspnea. BAP65 and DECAF scores also showed a correlation with length of stay. Conclusion: Objective and practical classifications are needed by clinicians to assess prognosis and initiate treatment accordingly. DECAF score is a strong candidate among severity indexes. Highlights of the StudyObjective and practical classifications are needed by clinicians in order to assess prognosis and initiate treatment accordingly in exacerbation of chronic obstructive lung disease.DECAF score with a cutoff value of 1 presented the highest sensitivity and BAP65 score with a cutoff value of 2 presented the highest specificity in predicting the need for ventilatory support.One-point increase in DECAF score created a 1.43 times higher risk of need for ventilatory support.